Parables of a Province - Parker, Gilbert, 1862-1932 (Salt Lake City, UT : Project Gutenberg, 2004)
"Parables of a Province" by Gilbert Parker is a collection of stories written during the late 19th century. The book explores themes of love, sacrifice, and the struggles of everyday people in a rural setting, centering around characters who often face life's challenges with courage and introspection. At the start of the book, we are introduced to Hepnon, a crippled dreamer who shares enchanting stories about the "Golden Pipes" of Margath Mountain. Renowned for his musical talent, Hepnon captures the hearts of locals through his violin and eventually dedicates himself to building a magnificent organ to replicate the ethereal music he believes echoes from the pipes at dawn and dusk. The first chapter sets a tone of mystical and poignant longing, showcasing Hepnon's tireless pursuit of beauty amidst his afflictions, culminating in a heart-wrenching performance that stirs deep emotions within his audience. The parables unfold to illustrate the intertwining of beauty and pain, suggesting that the quest for artistic expression is both a personal and collective experience. (This is an automatically generated summary.)
The golden pipes -- The guardian of the fire -- By that place called Peradventure -- The singing of the bees -- The white omen -- The sojourners -- The tent of the purple mat -- There was a little city -- The forge in the valley.
Release date is 2004-11-18
Produced by David Widger
Keywords: Short stories; Canadian fiction; Parables